2016
DOI: 10.1038/srep32303
|View full text |Cite
|
Sign up to set email alerts
|

Association of SCARB1 Gene Polymorphisms with Virological Response in Chronic Hepatitis C Patients Receiving Pegylated Interferon plus Ribavirin Therapy

Abstract: The scavenger receptor type B class I(SR-BI) is a receptor for high-density lipoproteins(HDL) and one of entry factors for hepatitis C virus(HCV). We examined the association of single nucleotide polymorphisms(SNPs) of the SCARB1 gene, which encodes SR-BI, with virologic responses to pegylated interferon-based treatment in Asian chronic hepatitis C(CHC) patients. Human genomic and clinical data were collected from 156 consecutive Taiwanese HCV genotype 1 or 2 patients who received pegylated interferon plus rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“… 122 Consequently, SCARB1 is strongly implicated in the pathogenesis of viral hepatitis and this is emphasized by the fact that patients with genetic variants of SCARB1 exhibit altered viral load 123 and virological responses. 124 125 Nevertheless, therapeutic targeting of SCARB1 with an antagonist in early-phase clinical trials demonstrated relatively low efficacy in HCV patients, suggesting a certain level of redundancy in its role. 126 127 In addition, and consistent with scavenger receptors being considered PRRs, one study has implicated both SR-AI and SCARF1 in the uptake and cross-presentation of HCV nonstructural (NS)3 protein by human myeloid cells (dendritic cells [DCs] and monocytes).…”
Section: Scavenger Receptors In Liver Disease Pathologymentioning
confidence: 99%
“… 122 Consequently, SCARB1 is strongly implicated in the pathogenesis of viral hepatitis and this is emphasized by the fact that patients with genetic variants of SCARB1 exhibit altered viral load 123 and virological responses. 124 125 Nevertheless, therapeutic targeting of SCARB1 with an antagonist in early-phase clinical trials demonstrated relatively low efficacy in HCV patients, suggesting a certain level of redundancy in its role. 126 127 In addition, and consistent with scavenger receptors being considered PRRs, one study has implicated both SR-AI and SCARF1 in the uptake and cross-presentation of HCV nonstructural (NS)3 protein by human myeloid cells (dendritic cells [DCs] and monocytes).…”
Section: Scavenger Receptors In Liver Disease Pathologymentioning
confidence: 99%
“…In previous reports, IFNL4 variants such as the major CC genotype of rs12979860, TT genotype of rs8099917 [30] and DG allele at rs368234815 [1] were found to be associated with spontaneous clearance of virus in individuals with acute HCV infection. Polymorphisms of other genes such as virus entry related SCARB1 gene [14] and MxA gene-rs2071430 TT genotype [32] also have shown association with spontaneous clearance or impaired clearance to HCV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic association of single nucleotide polymorphisms (SNPs) with HCV infections are mostly related to the host genes responsible for antiviral response or virus entry which either improve treatment induced clearance or promote/impair virus clearance against acute/chronic infections. In a recent study, HCV entry related SCARB1 (scavenger receptor type B class I) gene polymorphism was found to be associated with HCV RNA level and therapeutic response [14]. In earlier studies, IL28b polymorphisms (rs12979860G/C and rs8099917C/T) were found to be associated with sustained virological response (SVR) to pegylated IFN and ribavirin (PEG-IFN/RBV) therapy in both genome wide and candidate gene approach studies [10,29].…”
Section: Introductionmentioning
confidence: 99%
“…6 In contrast, the rs10846744 GG genotype (but not rs3782287) was associated with lower viral load in an Asian cohort, yet surprisingly was associated with a decreased sustained virological response (SVR) rate and unfavourable therapeutic outcomes in the context of pegylated interferon plus ribavirin therapy. 19 As these studies evaluated only pegylated interferon/ribavirin therapy, it would be interesting to further evaluate potential association between treatment outcome/kinetics in the era of DAA therapy. Given that these noncoding variants are relatively prevalent in human populations (minor allele frequencies between 25% and 42%), further studies in different populations are warranted to elucidate the relationship between non-coding SR-BI variants, HCV viral load and treatment outcome.…”
Section: See Article Pages 237-245mentioning
confidence: 99%